Responses of chloroplasts to stress conditions - Mittler, Ron (Henry Stewart Talks, 2007)
Environmental factors such as heat, drought or salinity can cause cell injury and death of plants, Within cells, chloroplasts contain many different mechanisms that enable them to cope with harsh environmental conditions and reduce risk associated with accumulation of toxic reactive oxygen species